2017
DOI: 10.15547/bjvm.1019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aflatoxin B1 alone or co-administered with Mycotox NG on performance and humoral immunity of turkey broilers.

Abstract: The contamination of poultry feeds with aflatoxins is a global problem responsible for considerable losses to poultry industry. The aim of the present investigation was to evaluate the effects of aflatoxin B 1 and Mycotox NG, applied either independently or together, on performance, relative weights of visceral organs and antibody titres against Newcastle disease in turkey broilers. Experiments of 42-day duration were carried out with sixty 7-day-old female turkey broilers (meat TM strain) divided into one con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The inter-layer characteristics known as 2:1 Phyllosilicate clay are made up of an octahedral sheet sandwiched as a planar structure between two tetrahedral sheets. Several reports have shown that 2:1 clay represents one of the most powerful prevention of aflatoxicosis in livestock [20,21,23,3133]. This could be because the planar molecule of aflatoxin can easily penetrate and bind into the interlayer of the planar 2:1 phyllosilicate clay structure.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-layer characteristics known as 2:1 Phyllosilicate clay are made up of an octahedral sheet sandwiched as a planar structure between two tetrahedral sheets. Several reports have shown that 2:1 clay represents one of the most powerful prevention of aflatoxicosis in livestock [20,21,23,3133]. This could be because the planar molecule of aflatoxin can easily penetrate and bind into the interlayer of the planar 2:1 phyllosilicate clay structure.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that adding phyllosilicate clay supplements to animal feed represents one of the most powerful prevention strategies for aflatoxicosis in livestock [21,55,56,57]. Heat treatment may alter the adsorbing properties of the clays, however, this has not been investigated much with respect to mycotoxins so far.…”
Section: Discussionmentioning
confidence: 99%
“…Trebak et al reported listlessness, anorexia [72]; other symptoms include poor feed utilization, stunted growth, decrease weight gain [73,74]; reduced egg weight and production. High levels of aflatoxins in broilers and turkeys cause hepatomegaly, fatty degeneration, fatty liver, bile conduct proliferation, periportal fibrosis, renal petechiations, tubular nephrosis, interstitial nephritis, and splenic atrophy [67,75].…”
Section: Effects On Poultrymentioning
confidence: 99%